Struktur Yoga Bali Kuno Pakem UHN I Gusti Bagus Sugriwa Denpasar: Sebuah Kajian Filosofis Dan Praktis - Suyanta, I Wayan; Sugata, I Made; Adi Brahman, I Made; Juniartha, Made G.; Alit Nuriawan, I Nengah (Jurnal Penelitian Agama Hindu, 2024)
Yoga and the spiritual activities of Balinese people are basically two things that cannot be separated. As Bali tourism develops, yoga, which was initially a religious activity in a physical (worldly) dimension, has metamorphosed into a tourism product. Ancient Balinese Yoga is a yoga activity that is explored and sourced from the local wisdom of the ancestors of the Balinese people which for UHN I Gusti Bagus Sugriwa has a responsibility to preserve and has great potential to be developed into tourist packages. This research is classified as research and development (R & D). Data is collected through technical observation, interviews and document study. The results of data analysis are presented in descriptive-narrative form. The research obtained results in the form of a philosophical explanation and benefits of the UHN I Gusti Bagus Sugriwa Denpasar Pakem Ancient Balinese Yoga. The UHN I Gusti Bagus Sugriwa DenpasarPakem of Ancient Balinese Yoga is the result of a combination of yoga teachings based on classical yoga texts, and three yoga colleges with an Ancient Balinese character in Bali, they are Seruling Dewata in Tabanan, the Windu Sara Foundation in Gianyar and Pasraman Bahung Tringan in Karangasem. In the philosophy of the UHN I Gusti Bagus Sugriwa Denpasar Pakem Ancient Balinese Yoga is a ritual process for self-purification to eliminate dirt or inner darkness that covers the existence of the Self (Soul). This process is carried out with self-discipline in the form of physical exercise (asana and pranayama), offerings (yajna), correct knowledge (jnana), tapa and samadhi. The yoga package products offered are a day yoga package (daily yoga), a 3 day yoga package (atelun yoga), a 1 week yoga package and a 2 week yoga package. The benefits of the UHN I Gusti Bagus Sugriwa Denpasar Pakem Ancient Balinese Yoga structure are projected to increase tourist attraction, strengthen cultural identity, improve community welfare, create jobs and increase income.